Tools of Lyapunov Functions for Qualitative Analysis of Time-Switched Linear System - Kuzmych, Olena I.; Aitouche, Abdel; Mekush, Oksana H.; Кузьмич, Олена Іванівна; Мекуш, Оксана Григорівна (My University, 2012)
We investigate a switched system given by a set of linear systems. We offer tools of qualitative system analysis using multiple Lyapunov function method and obtain an estimation of system solution at final time moment depending of initial state. The estimation is obtained by composing of perturbations of separate subsystems on each time interval of switched system.
Keywords: Lyapunov Functions; Time-Switched Linear System